Menegosiasikan Iman dan Makanan: Implementasi Kewajiban Sertifikasi Halal dalam Praktik Penggilingan Bakso Berbasis Komunitas di Pasar Tradisional Tanjung Morawa - Rizki Winanti; Cahaya Permata (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
Meatball grinding facilities process meat-based products and are therefore required to obtain halal certification due to several critical control points, such as meat sourcing, additives, hygiene, and potential contamination. However, none of the facilities at Pasar Rakyat Tanjung Morawa currently hold halal certification. This study investigates the factors hindering the implementation of Halal Product Assurance in these facilities. Using an empirical juridical approach, supported by a case study and sociological perspective, data were collected through observations and interviews, then analyzed qualitatively through deductive reasoning. The findings show that the main internal barrier is the lack of legal awareness among both business operators and consumers. Externally, challenges include limited supervision by BPJPH, the scarcity of halal-certified slaughterhouses (RPHU/RPHR), and the high costs of certification. Ensuring halal compliance in these facilities is crucial not only for improving food quality and safety but also for building consumer trust and ensuring access to products that meet halal standards.